Bell Palsy Mimics: Lessons from Four Malpractice Cases - Rachel Lindor; Summer Ghaith (Clinical Practice and Cases in Emergency Medicine)
Introduction: Bell palsy, an idiopathic dysfunction of the seventh cranial nerve, is the leading cause of unilateral facial paralysis, although other more serious entities such as stroke, infection, and tumor may present similarly, leading to both medical and legal risks in cases of misdiagnosis. Case Series: We present four malpractice cases revolving around misdiagnosis of Bell palsy. These cases alleged failure to diagnose, failure to obtain informed consent, and failure to provide appropriate discharge instructions. Outcomes ranged from a jury verdict in favor of the physician, to an out-of-court settlment for $400,000, to a jury verdict in favor of the patieint for over $3.1 million. Conclusion: Bell palsy is the most common cause of unilateral facial paralysis. While the diagnosis can be made at the bedside without advanced testing, doing so requires a clear understanding of the pathophysiology of the disease, an appreciation for the role of advanced diagnostics, and thorough documentation of a supportive history and physical exam. Misdiagnosis or mismanagement confers both clinical and legal risks.